Study on the anaerobic biotreatment of prednisone wastewater - TU Zhan; XIE Zuo-fu; ZHENG Ping; BIAN Lei; HE Yu-hui (浙江大学学报. 农业与生命科学版, 2007)
Prednisone wastewater is one of the industrial wastewaters that is very difficult to be treated. Since the BOD5/COD of the mixed prednisone wastewater was about 0.23, it was not easy to be treated biologically. After parts of the undissolved COD were removed by settlement, the BOD5/COD was up to 0.34. Because the COD∶N∶P of the mixed prednisone wastewater was 10415∶10∶1, additional N and P nutrients were required during anaerobic biotreatment. The results showed that the biotreatemnt of the mixed prednisone wastewaters with UASB process was feasible. When the hydraulic retention time (HRT) was set at 2 d and the volumetric loading rate was controlled between 4.16-4.98 g·L-1·d-1, the COD removal efficiency was kept higher than 80%. When the volumetric loading rate was higher than 5.96 g·L-1·d-1, the reactor was prone to acidification, but it could be recovered by decreasing the influent COD concentration and increasing the influent alkalinity.